Effects of brazing parameters on the microstructure and tensile shear force of copper sheets using amorphous filler metal - Prajak Jattakul; Kannachai Kanlayasiri (My University, 2018)
In this research, the objective was to investigate and measure the microstructure, tensile shear force, and fracture surface behavior when copper sheets are brazed using Cu-Ni-Sn-P amorphous filler metal. In order to examine the microstructure and its properties, assessment of the Cu-Ni-Sn-P/copper brazed joints was conducted after furnace brazing under an argon atmosphere using specific parameters relating to temperature, holding time, and loading pressure. In order to assess the tensile shear force, tensile testing was carried out. All the joints exhibited sound bonding without voids or cracks, when brazing temperatures reached 680 °C, this resulted in a maximum value for tensile shear force of 696.325 N. The microstructure consisted of both Cu-rich solid solution and a (Cu, Ni) 3 P phase as a eutectic structure formed in the brazing joint, and then the Cu-rich solid solution was produced as a matrix region around the eutectic structure. Fracture analysis was conducted for brazed joints which showed the ductile fractures after the shear test.
Keywords: Brazing; Shear Strength; Electronic Packaging and Soldering Technologies